Analysis of Production and Income of Fishermen Fishing Tools at Kepenghuluan Sungai Bakau, Sinaboi Sub-District, Rokan Hilir Regency, Riau Province - Orita Nadia Tamba; Hendrik Hendrik; Tince Sofyani (Faculty of Fisheries and Marine, Universitas Riau, 2024)
This research was conducted from November to December 2022 to analyze how much influence production factors influence the catch of trawl fishermen and know the income of fishermen who use trawl fishing gear in the Penghuluan Sungai Bakau, Sinaboi District, Rokan Hilir Regency Riau Province. The method used in this study was a survey that determined the sample using the total sampling or census method. The number of samples taken was 32 fishermen who used trawl fishing gear. The results of this study are the size of the ship and the length of time at sea affect the production of fishing trawler catch haul. In contrast, the number of crew members and experience at sea has no significant effect on fishing production with trawl fishing gear. The total net income or profit earned by fishermen is calculated for 20 trips/month, fishermen using 2 GT vessels amounting to IDR 25.496.044 and those using 3 GT vessels amounting to IDR 22.258.057 in peak season. In the middle season, fishermen's income is calculated for 20 trips/month using 2 GT vessels of IDR15.014.933 and those using 3 GT vessels of IDR12.386.628.